Effect of intrauterine and oral therapy during periparturient period in sow - SINGH, N K; SINGH, BALRAJ; SINHA, A K; SINGH, M P; SINGH, S K (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 73 sows of T x D (Tamworth x Desi) breed. The sows were attotted under sixgroups and various treatment viz. Gestaforte vet bolus (group T1), uterotone and (group T"), both orally andBetadine liquid intrauterine along with payapro bolus orally (group T3), and only Betadine liquid intrauterine(group T) were initiated within 24 hours of farrowing. Two groups (group C1 and C) were kept as control.Significantly (P
Keywords: Periparturient; litter weight; fertile estrus; post farrowing conception